Care needs and care consumption in psychosis: a 4-year longitudinal analysis of guideline concordant care. (19th November 2021) - Roebroek, L.; Bruins, J.; Roe, D.; Delespaul, P.; de Jong, S.; Boonstra, A.; Visser, E.; Castelein, S.
Abstract: Aims: People with psychotic disorders receive mental healthcare services mainly for their psychiatric care needs. However, patients often experience multiple physical or social wellbeing-related care needs as well. This study aims to identify care needs, investigate their changes over time and examine their association with mental healthcare consumption and evidence-based pharmacotherapy. Methods: This study combined annually obtained routine outcome monitoring (ROM) data with care consumption data of people with a long-term psychotic illness receiving treatment in four Dutch mental healthcare institutes between 2012 and 2016. Existing treatment algorithms were used to determine psychiatric, physical and social wellbeing-related care needs based on self-report questionnaires, semi-structured interviews and physical parameters. Care consumption was measured in hours of outpatient mental healthcare consumption per year. Generalised estimating equation models were used to calculate odds ratios of care needs and their associations with time, mental healthcare consumption and medication use. Results: Participants ( n = 2054) had on average 7.4 care needs per measurement and received 25.4 h of care per year. Physical care needs are most prevalent and persistent and people with more care needs receive more mental healthcare. Care needs for psychotic symptoms and most social wellbeing-related care needs decreased, whereas the chance of being overweight significantly increased with subsequent years of care. Several positive associations were found between care needs and mental healthcare consumption as well as positive relations between care needs and evidence-based pharmacotherapy. Conclusions: This longitudinal study present a novel approach in identifying care needs and their association with mental healthcare consumption and pharmacotherapy. Identification of care needs in this way based on ROM can assist daily clinical practice. A recovery-oriented view and a well-coordinated collaboration between clinicians and general practitioners together with shared decisions about which care needs to treat, can improve treatment delivery. Special attention is required for improving physical health in psychosis care which, despite appropriate pharmacotherapy and increasing care consumption, remains troublesome.